Inductively coupled plasma with mass-spectrometry method development and validation for gadolinium in gadolinium-based contrast agents of pharmaceutical formulations - Kona, Subramanya Srinivas; Changali, Mallesh; Kalva, Mahesh; Lakka, Narasimha Swamy (European Journal of Chemistry, 2020)
Gadolinium-based contrast agent interacts with the human body temporarily and improves the pictures of inside of the body produced by magnetic resonance imaging, computed tomography, X-rays and ultrasound and it also helps to distinguish the normal from abnormal conditions. In this study, the authors developed a simple, rapid, reliable and robust inductively coupled plasma mass-spectrometry method for estimation of gadolinium in gadolinium-based contrast agents to check the drug quality and ensure the patient safety. The samples were digested at 160°C using the microwave digestion system and the gadolinium was extracted in 0.4% (w/w) nitric acid. Interference of deposited gadolinium on sample cone and skimmer cone were investigated and evaluated. The developed method was validated as per ICH Q2 (R1) guideline and USP<730>. The precision was evaluated with six independent assays of gadolinium in each gadolinium-based contrast agent. The test method was found linear (r2 > 0.999) with five different levels covered from 25 200%, and accurate, mean recoveries were 92.5 107.5% at three different levels covered from 50 150%. The robustness was performed by changing the nitric acid concentration (0.4±0.04%, w/w) in diluent system. This method is suitable to quantitatively determine the amount of gadolinium in gadolinium-based contrast agent of drug products in presence of excipients used in formulation and also in drug substance.